A study on consumers’ perception towards Sara-Bif Products / Masri Haili - Haili, Masri (2002)
A study on consumers’ perception toward Sara-Bif products is seen to be very important as it can ascertain the poor response by the consumers towards the products. The poor response has resulted in the below-budget performance by the company. In fact, since its incorporation, no formal study has been conducted with regards to the acceptance of the product by the consumers. The below-budget performance of the company has prompted the shareholder and the initiating agency, SEDC Sarawak, to initiate the study on the sale of the product.